The Combining the Roles of a Teacher and an Artist: the Analysis of the Prospective Theatre Teachers’ Action Research - Kazragytė, Vida (Pedagogika, 2017)
The article deals with the empirical study, which inquiries in the combining the roles of an artist and of a teacher during artistic creation and education processes. The data were obtained by making the qualitative analysis of the accounts of the prospective theatre teachers’ action research reports (N – 24). The prospective theatre teachers were creating the theatrical performances and taught the students who performed the roles in their performances. There were not found any statements which would indicate that the roles of an artist and of a teacher are considered to be opposite to each other or hard to combine. The prospective theatre teachers are performing these roles in some types of combination: a) artist-teacher; b) artist- teacher specialist and 3) teacher-artist according to the different communication situations. During the performing of artist-teacher roles, communication with students is as if they were already artists. That is a way to raise the creative-artistic goals for students and encourage students to achieve them through learning. It can be said that this combination of roles is important, in view of the final objective. The artist- teacher specialist roles require to communicate with the imaginary artistic results (scenario), and the students work on the stage. In other words, to combine what is imaginary with what appears real. Also to determine which students’ skills are necessary to develop for the imaginary result to be closer to reality. This combination of roles is important, for to the evolving artistic result. According to the teacher-artist roles performing and communication is aimed at students “to grow up” to their actual role as artists. The teachers as artists take care of the development of the new students’ artistic abilities to be correct, based on what the students already have appropriate. And they try to develop the new student’s abilities needed for the performances. This makes the content of the education more purposeful and meaningful. The prospective theatre teachers do not mention any difficulties associated with the combining of roles. Only when the artistic creation and education processes slow down or are no longer productive, they analyzed their communication and found dissonance stemming from the loss of the role of a teacher. It can be assumed that this is due to lack of teaching experience and the fact that a lot of time and concentration has been spent on the communication in the world of imagination. Imbalance occurs also when they lack the knowledge of theory. The prospective theatre teachers combine the roles of an artist and of a teacher intuitively, without their explicit realisation. So, it is necessary to provide the students with knowledge about the combination of roles during the study process.